2023
DOI: 10.1186/s12870-023-04254-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of straw decomposition and rice growth through co-application of straw-decomposing inoculants and ammonium nitrogen fertilizer

Abstract: Background The growth of rice is reduced by the slow decomposition of accumulated straw, which competes with rice for soil nitrogen nutrient. In recent year, straw-decomposing inoculants (SDIs) that can accelerate straw decomposition and ammonium nitrogen (N) fertilizer that can quickly generate available N is increasingly adopted in China. However, it is still unknown whether the N demand of straw decomposition and crop growth can be simultaneously met through the co-application of SDIs and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The SCP fertigation might have led to increased nitrogen exposure to the straw. This aligns with Liu et al's study [49], which found that higher nitrogen levels supported a faster rate of straw decomposition. There was no notable difference between the crude fiber content of the three groups of straws when SCP fertigation was applied.…”
Section: Effect On the Crude Fiber Content Of Strawsupporting
confidence: 91%
“…The SCP fertigation might have led to increased nitrogen exposure to the straw. This aligns with Liu et al's study [49], which found that higher nitrogen levels supported a faster rate of straw decomposition. There was no notable difference between the crude fiber content of the three groups of straws when SCP fertigation was applied.…”
Section: Effect On the Crude Fiber Content Of Strawsupporting
confidence: 91%
“…There are reports indicating that ammonium-N tends to be more readily retained when the paddy field is supplemented with CF [47,48]. Such an irrigation regime greatly facilitates the efficient and rapid uptake of nitrogen by the rice roots, which, traditionally, is highly advantageous for rice growth and development, such as more tiller numbers and higher total LAI [49,50]. In contrast, these parameters were all decreased in the AWMD regime (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 96%